Optical multiple-image authentication scheme based on the phase retrieval algorithm in gyrator domain. (3rd April 2017) - Sui, Liansheng; Zhang, Xiao; Tian, Ailing
Abstract: A novel optical multiple-image authentication scheme based on the phase retrieval algorithm is presented in gyrator domain. According to a plain image, only one phase-only mask is obtained as the encrypted result by using the proposed phase retrieval algorithm, which has a fast convergence rate and good performance on mean square error. Afterwards, the sparsely encrypted distribution is extracted from the phase-only mask by selecting a certain percentage of pixels randomly. Different from other multiple-image authentication system based on space multiplexing, all sparsely encrypted distributions of plain images are finally integrated into the ciphertext by making use of the inter-modulation operation of phase masks, where the decryption process can be performed efficiently without any cross-talk noise and the encrypted capacity is nearly unlimited. Only when the secret keys are correct, the content of the plain images can be authenticated, in which the authentication process can be implemented optically by using the architecture of double random phase encoding. Simulation results are given to demonstrate the feasibility and robustness of the proposed scheme.